Producción y exportación de la fruta pitahaya hacia el mercado europeo - Jordán Molina, Diana (2009)
The fruit Pitahaya has diverse uses and benefits nevertheless its consumption mainly is done as fresh fruit with numerous healthy properties for the human body. The cultivation of the fruit is relatively new in the Ecuador. We find varieties that were introduced from Colombia, being this country the pioneer in exports to the International market. The current exports of Colombia and Guatemala, barely cover the 25% of the total demand of the international market, being the main consumer the European market; creating an opportunity for the development of the “present project”. We have to emphasize that the investment in this project, not only will bring benefits to its owners but will create new opportunities for fruits and for non traditional products creating multiple effects over the local economy. The zone of production is focused to be done in the Ecuadorian Oriente Basin, because it reaches the greater level of productivity. Its exportation will be directed to companies specialized in the commercialization of this “non traditional product”. The present project includes: a detailed study of the variables that should take into account, a description of the process, analysis of the requirements for infrastructure as well as the adequate equipment for a successful production operation and the proof that this project itself is feasible based on its profit results.